Comparison between lidocaine and nacl 0.9% inhalation in heart rate and blood pressure changes during laryngoscopy and intubation - Soenarto, Ratna Farida; Pryambodho, Pryambodho; Adji, Muhammad Prakoso (Bali Journal of Anesthesiology, 2019)
Introduction: Laryngoscopy and intubation is an invasive procedure routinely done during general anesthesia. The cardiovascular response to these procedures can be harmful in patients who are vulnerable, especially those who have cardiac or cerebrovascular problems. One method to attenuates the cardiovascular response was the use of anesthetics, including lidocaine. This study aimed to assess the effect of inhaled lidocaine on cardiovascular responses after laryngoscopy and intubation.Patients and Methods: This study was a randomized double-blind clinical trial on 50 subjects who underwent elective surgery, 24 subjects were given inhaled lidocaine 1.5 mg/kg and 25 subjects were given 0.9 % NaCl inhalation before laryngoscopy and intubation. Cardiovascular parameters being investigated were changes in systolic and diastolic blood pressure, mean arterial pressure (MAP) and heart rate in a serial manner.Results: In the first minute after intubation, MAP and heart rate were higher in the NaCl group. The difference in MAP was 15.5 mmHg (p <0.001) while heart rate was 9.5 beats/min (p <0.001). In the 3rd minute after intubation, MAP and heart rate kept different in both groups: 16.6 mmHg (p <0.001) and 11.2 beats/minute (p <0.001), respectively. In the 5th minute after intubation, MAP and heart rate remained different between two groups: 16.7 mmHg (p <0.001) and 10.0 beats/min (p=0.03), respectively.Conclusion: Lidocaine inhalation was able to attenuate cardiovascular response due to pain stimuli and sympathetic stimulation after laryngoscopy and intubation.